An inclusive approach to searching for evidence on EdTech in low- and middle- income countries - Brugha, Meaghan (The EdTech Hub, 2020)
A blog post by Meaghan Brugha and Katy Jordan. A searchable database The EdTech Hub has undertaken a large-scale search for publications on technology use in education in low- and middle- income countries. During this process, we created an internal research database. This is searchable through the use of a variety of filters, such as …
EdTechHub.Source: 2405685:BGLPB3AG KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911079 2129771:86J5A5RJ 2405685:BGLPB3AG
Keywords: _C:Gambia GMB; _C:Jordan JOR; _C:Malawi MWI; _C:Portugal PRT; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _zenodoODE